From the diaries of V.O. Klyuchevsky, 1904–1905 - KlyuchevskyV. (Voprosy obrazovaniya / Educational Studies Moscow, 2010)
This section presents unique documents: unpublished fragments of V.O. Klyuchevsky’s notebooks and diaries of 1904–1905, in which he analyses the logic of the dramatic events of those years. His musings are centered about questions of culture and education as a possible escape from the bacchanal of uncontrollable historical forces. Questions of university education, ponderings on what history is, what the role of the university in Russian political life is, connect various separate observations into a harmonious whole. The diary chronicals assumes the character of a history of ideas.